Determination of Optimal Size of Government in Relation to Output Growth in Nigeria: A Monte Carlo Simulation Evidence - Umoru, David (Faculty of Economics, Universitas Sriwijaya, 2020)
This paper attempted to estimate optimal size of public sector that prompts positive output growth in Nigeria based on Monte Carlo simulation of estimated parameters of an error correction model having controlled for regime effect. Our motivation derives from economic theory that absence of government could be injurious to output growth culminating in unavailability of contracts and public goods. Using different policy scenarios of public sector share in GDP, the study validates and supports the tenets of Rahn Curve that economy shrinks when government grows enormous as we found 40% public sector spending as proportion of GDP as optimal public sector size that stimulates positive growth rate of about 0.095% having controlled for regime effect. By implication, our original contribution in this study is amplified on our empirics that public sector role in Nigerian economy is less than or equal to 40%. Consequently, any size of public sector beyond forty percent is economically destructive as it capable of stimulating negative spill overs on the economy due to growing taxes and public debt repayment. Hence, public sector spending should be significantly less than forty percent or at most forty percent for purpose of economic growth. This indeed translates to enforcing responsible fiscal policy centred on forty percent public sector size.